(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2016)
The Rainfall Intensity-Duration-Frequency (IDF) relationship is one of the most commonly used tools in water resources engineering, either for planning, designing and operating of water resource projects or for various engineering projects against floods. The objective of this study is to develop an empirical formula to estimate rainfall intensity for any duration and any return period with minimum effort. Daily rainfall data for years 1980-2010 from Iraqi Metrological Organization and Seismology was used in this study. Hershfeildʼs method was used to estimate the short duration rainfall intensity from daily rainfall data. Various distribution functions were used for analysis and Chi-Square goodness to fit test were used to identify the best statistical distribution among them. Study showed that Log Pearson type III is the best probability distribution and the best (IDF)empirical formula was in the form [i=a/(b=td)]